Gangguan Digital dan Evolusi Budaya Organisasi: Menguraikan Dinamika Teknologi Kerja Jarak Jauh - Junita Sari Ismail; Rubah Indah Dermawati; Adi Lukman Hakim; nuning nurna dewi (JEB17 : Jurnal Ekonomi dan Bisnis, 2026)
Organizational culture change has become a critical issue in the digital disruption era, which demands rapid adaptation to new technologies and virtual work patterns. This article reviews literature on how digital transformation drives cultural evolution by integrating two theoretical frameworks: Kotter’s eight-step model (1996) and complexity theory (Stacey, 2000). The hybrid model combines strategic direction (top-down) with adaptive emergence (bottom-up), aligned with Indonesia’s collectivist cultural context. Using a systematic literature review and thematic synthesis of 25 relevant articles, findings reveal that digital-era cultural change is non-linear and emerges through intertwined technological and social interactions. The proposed hybrid model provides a contextualized framework for managing sustainable organizational culture change. Keywords: organizational culture, digital disruption, complexity theory, Kotter model, organizational change